Mentoring Interventions for Underrepresented Scholars in Biomedical and Behavioral Sciences: Effects on Quality of Mentoring Interactions and Discussions - Lewis, Vivian (CBE Life Sci Educ, 2017)
Mentors rarely receive education about the unique needs of underrepresented scholars in the biomedical and behavioral sciences. We hypothesized that mentor-training and peer-mentoring interventions for these scholars would enrich the perceived quality and breadth of discussions between mentor–protégé dyads (i.e., mentor–protégé pairs). Our multicenter, randomized study of 150 underrepresented scholar–mentor dyads compared: 1) mentor training, 2) protégé peer mentoring, 3) combined mentor training and peer mentoring, and 4) a control condition (i.e., usual practice of mentoring). In this secondary analysis, the outcome variables were quality of dyad time and breadth of their discussions. Protégé participants were graduate students, fellows, and junior faculty in behavioral and biomedical research and healthcare. Dyads with mentor training were more likely than those without mentor training to have discussed teaching and work–life balance. Dyads with peer mentoring were more likely than those without peer mentoring to have discussed clinical care and career plans. The combined intervention dyads were more likely than controls to perceive that the quality of their time together was good/excellent. Our study supports the value of these mentoring interventions to enhance the breadth of dyad discussions and quality of time together, both important components of a good mentoring relationship.